Problems of application of law in the metaverse - an open Pandora's box - Marčiulaitytė, Gabija; Grybauskaitė, Dominyka (Vilnius University Open Series, 2024)
The concept of metavisata is becoming increasingly relevant in the modern world surrounded by technologies and innovations. The creation of an alternative reality - a meta world - not only unlocks the gates to a space of infinite possibilities and experiences, but at the same time opens a Pandora’s box of legal problems. This work analyses the specific problems of intellectual property and personal data protection in the meta world and provides solutions to these issues.The article also highlights the origin and meaning of metavisata as a concept, the components and threats of this technology. A detailed analysis of Lithuanian and foreign literature, international and national legislation reveals the problems of the application of law in the metaverse. This work concludes that the relations and civil circulation in virtual reality should be regulated not only by technical measures, but also by legal instruments, which would ensure legal accuracy and certainty and, finally, protect the consumer’s property, privacy and other inherent rights.
Keywords: metaverse; legal issues; intellectual property; personal data protection